1978
DOI: 10.1128/aac.13.6.910
|View full text |Cite
|
Sign up to set email alerts
|

Iodometric Assay Method for Beta-Lactamase with Various Beta-Lactam Antibiotics as Substrates

Abstract: The rapid fixed-time assay for penicillinase was modified for measuring β-lactamase activity with twelve substrates, i.e., benzylpenicillin, ampicillin, cloxacillin, methicillin, carbenicillin, cefazolin, cephalothin, cephaloglycin, cephalexin, cephalosporin C, 7-aminocephalosporanic acid, and cefoxitin. The method depends upon the reduction of iodine by the hydrolyzed substrate. Determined experimentally, 1 mol of hydrolyzed penicillins consumed 3.4 to 4.0 mol of iodine (I 2 ). Iodine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(42 citation statements)
references
References 4 publications
1
41
0
Order By: Relevance
“…For routine assay, f3-lactamase activity was determined iodometrically at 30 C in 0.1 M phosphate buffer (pH 7.0) by the method of Perret (21) or a colorimetric method (28). A microiodometric assay method (19) or a pH-stat method (25) was employed for the determination of kinetic parameters.…”
Section: Methodsmentioning
confidence: 99%
“…For routine assay, f3-lactamase activity was determined iodometrically at 30 C in 0.1 M phosphate buffer (pH 7.0) by the method of Perret (21) or a colorimetric method (28). A microiodometric assay method (19) or a pH-stat method (25) was employed for the determination of kinetic parameters.…”
Section: Methodsmentioning
confidence: 99%
“…β-lactamase enzyme activity was calculated by formula described by Sawai T et al (11) . The enzymatic activity which is defined as the consumed amount was determined experimentally for β-lactam antibiotic with the interval of time.…”
Section: β-Lactamase Assay Resultsmentioning
confidence: 99%
“…The quantity of the hydrolyzed substrate in reaction tubes was calculated by the following formula of enzyme activity which is defined as the quantity that hydrolyzed 1µmol of substrate per minute of time under the condition used. (11,13) .…”
Section: In Presence Of Enzyme (Produced By Strain)mentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by Bush K that up to eight types β-lactamases are produced by a single strain (15) . Iodometric assay for the analysis of β-lactamases has previously been compared by Shivali VG et al with acidometric and disk diffusion methods and reported as the most convenient and reliable method (16) , Sawai T et al has also worked on the iodometric assay for the same enzyme and stated the efficacy of this technique to quantify the β-lactamase production (11) . In this study idometric analysis of the studied strain assay gave the noteworthy result that can be use in further research, though to increase the purity of the crude enzyme chromatography can be useful.…”
Section: Discussionmentioning
confidence: 99%